A Study of Daylight Optimization in Building Design in The Student’s Residential College of UTHM Pagoh - Ku Adzman, Ku Nur Farzana; Nurdalila Saji; Mohd Arish, Nur Aini (Journal of Advanced Industrial Technology and Application, 2020)
Daylight is often used as a natural light source in order to reduce the consumption of energy in a building and maintain sustainability during the daytime. This study finds that the residential college design is lacking of passive solar control devices to control the daylight penetration into the building which causes discomfort due to direct sunlight problems. This paper identified and analyzed the daylighting performance of the residential college’s living area via computer simulations. The daylight performance for the living area of the residential college has been investigated in terms of daylight factor and indoor illuminance. The excessive amount of daylight penetration in the living area can be optimized by upgrading the windows with external shading devices. An external shading device is proposed in this study to avoid the intensity of solar radiation and transfer direct sunlight into the living area. The external shading device design is chosen suitably to the building design. SketchUp software is used to simulate the building design into two 3D models, the first model is a building without shading devices and the second model is a building with shading devices. The 3D models are converted into 2D models using VELUX Daylight Visualizer software. Daylight factor and indoor illuminance are analyzed using VELUX Daylight Visualizer software to calculate the extent of daylight penetrations. Then, the results generated by VELUX Daylight Visualizer software are used to compare the building without shading devices and the building with shading devices. The results showed that the building with shading devices installation are more effective in optimizing the daylight penetration. Therefore, shading devices should be included in the design of the residential colleges to create a comfortable thermal condition for the occupants.